2019
DOI: 10.1111/hex.12993
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and providers’ perspectives on medication relatedness and potential preventability of hospital readmissions within 30 days of discharge

Abstract: Background: Hospital readmissions are increasingly used as an indicator of quality in health care. One potential risk factor of readmissions is polypharmacy. No studies have explored the patients' perspectives on the medication relatedness and potential preventability of their readmissions. Objective:To compare the patients' perspectives on the medication relatedness and potential preventability of their readmissions with the providers' perspectives. Methods:Patients unplanned readmitted within 30 days after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We found evidence that communication of the medication-relatedness of the readmission was present in 58% of readmissions. A previous study showed that patients’ and healthcare providers’ perspectives on the medication-relatedness of readmissions and their preventability differed ( Uitvlugt et al, 2020 ). Consensus between patients and healthcare providers with respect to the role of medication is necessary to achieve optimal pharmacotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found evidence that communication of the medication-relatedness of the readmission was present in 58% of readmissions. A previous study showed that patients’ and healthcare providers’ perspectives on the medication-relatedness of readmissions and their preventability differed ( Uitvlugt et al, 2020 ). Consensus between patients and healthcare providers with respect to the role of medication is necessary to achieve optimal pharmacotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, cooperation between healthcare providers and patients may improve recognition of MRRs. Uitvlugt et al showed that patients could offer more medication-related information (e.g., non-adherence) regarding the period after discharge than healthcare providers because this information is often not documented in the patient records ( Uitvlugt et al, 2020 ). Therefore, a patient interview regarding the reason of readmission should be implemented to improve recognition of an MRR.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these important factors include structured documentation of cognitive impairment index 29 , 30 , health literacy of patients, frailty scores 31 , and social environment factors 32 35 . Also, the points of view of primary care providers and patients should ideally be included 36 , especially as there is evidence that readmissions after 7 days could be prevented in the non-hospital environment 19 .…”
Section: Discussionmentioning
confidence: 99%